DAMPAK PROGRAM IbPE BAGI UKM GULA KELAPA DI KABUPATEN BANYUMAS PROVINSI JAWA TENGAH - Suliyanto Suliyanto; Weni Novandari; Mustaufik Mustaufik (Media Ekonomi, 2017)
IbPE program aims to increase the export growth of SMEs Coconat-Sugar through increased production, increased sales, improved quality of coconut sugar accompanied by increased management of activity. This program was conducted by the method of training, mentoring and enhance production facilities according with a target of SMEs Ngudi Lestari and SMEs Lestari Jaya in Kalisalak Village, Kebasen sub-district, Banyumas district during the years 2014-2016. Based on the differences analysis in performance of SMEs was concluded there is an increased performance of SMEs based on the indicators of the amount of production, turnover, export, labor, and there is an increase in production management , human resource management, financial management. Keyword : Coconut Sugar, Small Medium Enterprises, IbPE